2020
DOI: 10.1080/1331677x.2020.1836992
|View full text |Cite
|
Sign up to set email alerts
|

Research model for measuring the impact of customer relationship management (CRM) on performance indicators

Abstract: Customer Relationship Management (CRM) has established itself as one of the fastest growing business management technology solutions in recent years, which makes it a key tool for companies that seek sustainable commercial success over time. The three CRM modules (sales, marketing, and services) are a definitive tool to obtain better business results through the customer-centred approach of modern marketing theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 57 publications
0
23
0
7
Order By: Relevance
“…Atendiendo a estudios previos sobre diferentes modelos de validación empírica sobre el impacto de uso de CRM (Guerola-Navarro et al, 2020b;Valmohammadi, 2017;Calantone et al, 2002;Zegarra, 2014), se ha considerado elegir las siguientes variables de studio:…”
Section: Elección De Las Variablesunclassified
See 2 more Smart Citations
“…Atendiendo a estudios previos sobre diferentes modelos de validación empírica sobre el impacto de uso de CRM (Guerola-Navarro et al, 2020b;Valmohammadi, 2017;Calantone et al, 2002;Zegarra, 2014), se ha considerado elegir las siguientes variables de studio:…”
Section: Elección De Las Variablesunclassified
“…Uno de los sistemas de gestión que se presenta como más eficiente y de mayor impacto para que las empresas puedan afrontar con éxito sus procesos de transformación digital, es la solución tecnológica CRM, que surge (junto con los sistemas ERP) como una de las soluciones de negocio con mayor impacto y relevancia en la actualidad (Vicedo et al, 2020;Gil-Gomez et al, 2020). CRM es una de las tecnologías clave en este proceso de transformación digital, tanto por las mejoras de gestión internas que puede y debe atraer a la empresa (en cuanto a mejora y más eficiente gestión de las relaciones con los clientes) como por el impacto que ello puede tener en el mantenimiento y potenciamiento de la ventaja competitiva de la empresa en el mercado (Guerola-Navarro et al, 2020b).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Для создания информационной системы требуется привлечение трудовых и материальных ресурсов. Основное требование, влияющее на архитектуру и инфраструктуру информационной системы, является минимизация ее совокупной стоимости [7][8].…”
Section: Development Of Web-application With Crs-system For Anti-collection Activitiesunclassified
“…The positive effects on profitability and sustainability over time, laying our customers is a strategic objective for companies and a central focus of marketing efforts (Eide et al, 2020;Gil et al, 2020 ;). Previous reports have found that consumer retention costs are considerably smaller than acquisition expense relative (Guerola et al, 2020;You et al, 2020), with companies investing significantly on customer satisfaction construction and administration (Morgeson et al, 2020). For example, annually spending on consumer loyalty services in the United States alone has risen by 27 percent in 2010, to more than US$48 billion through USD2.7 billion .…”
Section: Brand Loyaltymentioning
confidence: 99%